Features of intercity bus passenger group mobility behaviors in the context of smart tourism - Han, Shao-Yong; Zhan, Jing-Chun; Xie, Cui-Hua; Wang, Zhen (Frontiers in Physics, 2022)
The features of intercity bus passenger group mobility behaviors have important guiding significance for the transportation department. Based on passengers’ intercity bus ticket reservation records (roundtrips from Shanghai or Chongqing city) from a smart tourism app, the travel behaviors of these two groups of bus passengers are analyzed and compared. In each group, the passengers’ travelling interval time presents a power-law with a cutoff index, and the passengers’ travelling behaviors have negative memory and low burstiness. Also, travel distance displays a scale-free property, and it is more likely to have an exponential distribution. Furthermore, the difference in cyclotron radius between these two groups’ travelling distances is quite significant; roundtrips from Shanghai are frequent. Last, holidays have a significant influence on passengers’ travel behaviors, which leads to more trips. The research conclusions are helpful to deeply understand the features of human mobility behavior in theory, and can assist the transportation department in traffic planning in the application.